Stochastic resonance and the homoeopathic effect - Torres, José-Leonel; Ruiz, Ma Guadalupe (British Homeopathic Journal, 1996)
Potentization of homoeopathic medicines by successive dilutions and succussion at each step is interpreted in terms of stochastic resonance, a non-linear response of certain systems when perturbed by noise and a weak periodic signal, which increasingly enhanced at the output as the magnitude of the noise grows towards an optimal value for maximum signal amplification. The possible relevance of stochastic resonance in other physiological phenomena like the kindling effect, where epileptic convulsions are induced in rats and other animals by periodic stimulation of the brain with weak electric signals, is also considered.